Ensuring system integrity and security on limited environment systems - Jauhiainen, Juho (My University, 2021)
Cyber security threats have rapidly developed in recent years and should also be considered when building or implementing systems that traditionally have not been connected to networks. More and more these systems are getting networked and controlled remotely, which widens their attack surface and lays them open to cyber threats. This means the systems should be able to detect and block malware threats without letting the controls affect daily operations. File integrity monitoring and protection could be one way to protect systems from emerging threats. The use case for this study is a computer system, that controls medical device. This kind of system does not necessarily have an internet connection and is not connected to a LAN network by default. Ensuring integrity on the system is critical as if the system would be infected by a malware, it could affect to the test results. This thesis studies what are the feasible ways to ensure system integrity on limited environment systems. Firstly these methods and tools are listed through a literature review. All of the tools are studied how they protect the system integrity. The literature review aims to select methods for further testing through a deductive reasoning. After selecting methods for testing, their implementations are installed to the testing environment. The methods are first tested for performance and then their detection and blocking capability is tested against real life threats. Finally, this thesis proposes a method which could be implemented to the presented use case. The proposal at the end is based on the conducted tests.
Keywords: file integrity monitoring, FIM, RIM, limited environment, IoT